Classical fluctuation electrodynamics - Sokolovsky, A.I.; Stupka, A.A. (Condensed Matter Physics, 2005)
A system consisting of an equilibrium medium formed by charged particles
and electromagnetic field is considered in the classical case at weak
interaction between subsystems. The field is described with all the statistical
moments of electric and magnetic fields. The moments are reduced
description parameters of the herein developed theory based on the Bogolyubov
reduced description method of nonequilibrium states. The generalized
Bogolyubov condition of the complete correlation weakening between
the subsystems is used as a boundary condition to the Liouville
equation. Distribution function of the system is calculated up to the third order
in electromagnetic interaction. Time equations for the reduced description
parameters are written in a compact form using a generating functional
for the field moments and a generating functional for field correlations
(centered moments, fluctuations). The obtained equations generalize the
nonlinear electrodynamics in equilibrium media for the case of fluctuations
of electromagnetic field being taken into account. Cистема, яка складається з рівноважного середовища із заряджених частинок і електромагнітного поля, розглянута в класичному
випадку та при малій взаємодії між підсистемами. Функцію розподілу системи розраховано з точністю до третього порядку за електромагнітною взаємодією. Поле описується усіма моментами електричного та магнітного поля, які обрані параметрами скороченого
опису в рамках метода скороченого опису нерівноважних станів
Боголюбова. Як гранична умова до рівняння Ліувілля застосована
узагальнена умова Боголюбова повного ослаблення кореляцій між
підсистемами. Одержані часові рівняння для параметрів скороченого опису записані в компактній формі за допомогою породжуючого функціоналу для моментів поля та породжуючого функціоналу
для кореляцій поля (центрованих моментів, флуктуацій). Отримані
рівняння узагальнюють нелінійну електродинаміку в рівноважному
середовищі на випадок врахування флуктуацій електроманітного
поля.